The Integration of Ministry and Secular Work - Tololiu, Wirna (International Journal of Education, Information Technology, and Others, 2025)
This study investigates the integration of pastoral ministry and secular work through a theological-exegetical inquiry into the Apostle Paul’s model in 1 and 2 Thessalonians, with a particular focus on bivocational pastors in Minahasa, Indonesia. The research is motivated by growing tensions within local churches where pastors are compelled to engage in secular employment due to economic necessity, raising theological and ethical questions about the legitimacy of such practices. The aim of this study is to examine whether bivocational ministry, as practiced by many Minahasan pastors, aligns with Paul’s vision of responsible, self-sustaining spiritual leadership. Using a qualitative approach that combines exegetical analysis of key biblical texts (1 Thess. 2:9 and 2 Thess. 3:6–12) with field data collected from interviews and observations involving ten pastors across multiple denominations, the study provides a contextual reading of Paul’s ethic of labor and ministry. The findings reveal that 70% of participants engage in additional work such as farming, teaching, or trading—not as a distraction from their calling, but as an intentional way to embody their faith in daily life. Rather than compromising their pastoral identity, this practice expands their relational influence and moral credibility in the community. This research concludes that bivocational ministry, when carried out with theological awareness and pastoral integrity, is a valid and contextually faithful expression of Christian vocation. The study affirms the need for a flexible theological paradigm that acknowledges diverse models of ministry, while calling on churches to support their pastors according to their capacity and context.